2013
DOI: 10.1186/cc12739
|View full text |Cite
|
Sign up to set email alerts
|

The 372 T/C genetic polymorphism of TIMP-1 is associated with serum levels of TIMP-1 and survival in patients with severe sepsis

Abstract: IntroductionPrevious studies have found higher circulating levels of tissue inhibitor of matrix metalloproteinase (TIMP)-1 in nonsurviving septic patients than in surviving septic patients, and an association between the 372 T/C genetic polymorphism of TIMP-1 and the risk of developing certain diseases. However, the relationship between genetic polymorphisms of TIMP-1, circulating TIMP-1 levels and survival in patients with severe sepsis has not been examined, and this was the objective of the study.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
(37 reference statements)
5
32
0
Order By: Relevance
“…However other studies have reported that carriers of the 6A6A genotype of this MMP-3 SNP had higher plasma MMP-3 levels202122232425262728293031323334. Our results were similar to the latter studies although only in septic patients but not in the uninfected controls, which is intriguing and needs further exploration.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However other studies have reported that carriers of the 6A6A genotype of this MMP-3 SNP had higher plasma MMP-3 levels202122232425262728293031323334. Our results were similar to the latter studies although only in septic patients but not in the uninfected controls, which is intriguing and needs further exploration.…”
Section: Discussionsupporting
confidence: 86%
“…TIMP-1 has been proposed as a useful laboratory marker to predict the clinical outcome of septic patients1011. Furthermore, carriers of the T allele in the TIMP-1 (372 T/C) SNP (rs4898) showed higher serum TIMP-1 levels and lower survival rate among septic patients in one study27. The low death rate among septic patients in our cohort (7.8%) has limited the statistical significance of TIMP-1 and the rest of data analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The TIMP-1 gene is located on the X chromosome. Due to the nature of the analysis in Xlinked gene polymorphisms, there might be larger or no difference seen in genotypic distribution of this variant regarding the gender [19,48]. In this study, the 372 T/C polymorphism of TIMP-1 was significantly associated with EH (p=0.000) among Malay males.…”
Section: T/c Polymorphism Of Timp-1 Genementioning
confidence: 57%
“…Circulating levels of TIMP-1 were associated with Left ventricular diastolic impairment in hypertensives [11]. The TIMP-1 372 T/C polymorphism (rs4898) resulted from T to C substitution at position 372, was shown to be associated with survival rate in sepsis [19] and crohn's disease [48]. However, the association between 372 T/C gene polymorphism of TIMP-1, was not determined in hypertensive subjects.…”
Section: T/c Polymorphism Of Timp-1 Genementioning
confidence: 99%
See 1 more Smart Citation